2017
DOI: 10.1128/jvi.00007-17
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Couples NF-κB/RelA with Airway Inflammation and the IRF-RIG-I Amplification Loop in Respiratory Syncytial Virus Infection

Abstract: The airway mucosa expresses protective interferon (IFN) and inflammatory cytokines in response to respiratory syncytial virus (RSV) infection. In this study, we examine the role of bromodomain containing 4 (BRD4) in mediating this innate immune response in human small airway epithelial cells. We observe that RSV induces BRD4 to complex with NF-B/RelA. BRD4 is functionally required for expression of the NF-Bdependent inflammatory gene regulatory network (GRN), including the IFN response factor 1 (IRF1) and IRF7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(148 citation statements)
references
References 79 publications
(130 reference statements)
10
138
0
Order By: Relevance
“…The immune response to RSV infection differs between mouse strains . Within C57BL/6 mice, there is a clear role for Type I IFNs as well as IFNAR in RSV infection . We also chose the C57BL/6 background to exclude any pollen effect mediated by allergic sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to RSV infection differs between mouse strains . Within C57BL/6 mice, there is a clear role for Type I IFNs as well as IFNAR in RSV infection . We also chose the C57BL/6 background to exclude any pollen effect mediated by allergic sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Although IRF3 activation is largely NFκB-independent, sustained IRF action on IFN and ISG expression requires ongoing NFκB signaling in epithelial cells. Some key elements of NFκB-IRF pathway cross-talk are that: (1) the virus infection-activated IFNβ enhanceosome is activated by NFκB (note that IFNβ is a major type I IFN, responsible for the majority of mucosal anti-viral effect); (2) the induction of inducible IRF-1 and -7 subunits controlling type I IFN expression are dependent on direct NFκB transactivation [33]; and, (3) NFκB is required for the IRF-IFN-RIG-I amplification loop, described above [34]. Consequently, sustained epithelial IFN response is substantially blunted in the absence of NFκB [33,34].…”
Section: Activation and Cross-talk Of The Nfκb And Irf3 Pathways In Rmentioning
confidence: 99%
“…The essential functional role of CDK9•BRD4 in RSV-induced IIR has been demonstrated by disruption of P-TEFb recruitment by RelA Ser 276 site mutation [52], siRNA-mediated silencing of CDK9 and BRD4 [24,52,53,61], and small-molecule inhibition of CKD9 and BRD4 [34,48,53]. Consequently, CDK9•BRD4 are molecules receiving significant attention as a target for pharmacological manipulation of viral and allergen-inducible mucosal inflammation [48,[62][63][64][65][66].…”
Section: Mechanism Of Transcriptional Elongation In the Iirmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports demonstrated that Brd4 plays a major role in the pathogenesis of airway inflammation. Indeed, Brd4 activation in bronchial epithelial cells was induced by several inflammatory stimuli, such as RS virus, and diesel exhaust particles that are able to exacerbate airway inflammation [28, 29]. In addition, Brd4 regulates IL-1β-induced IL-8 expression in airway epithelial cells [30].…”
Section: Discussionmentioning
confidence: 99%